Sub-micrometer Geometrically Encoded Fluorescent Barcodes Self-Assembled from DNA - Lin, Chenxiang (2012)
The identification and differentiation of a large number of distinct molecular species with high temporal and spatial resolution is a major challenge in biomedical science. Fluorescence microscopy is a powerful tool, but its multiplexing ability is limited by the number of spectrally distinguishable fluorophores. Here we use DNA-origami technology to construct sub-micrometer nanorods that act as fluorescent barcodes. We demonstrate that spatial control over the positioning of fluorophores on the surface of a stiff DNA nanorod can produce 216 distinct barcodes that can be unambiguously decoded using epifluorescence or total internal reflection fluorescence (TIRF) microscopy. Barcodes with higher spatial information density were demonstrated via the construction of super-resolution barcodes with features spaced by ~40 nm. One species of the barcodes was used to tag yeast surface receptors, suggesting their potential applications as in situ imaging probes for diverse biomolecular and cellular entities in their native environments.